A Culture of News. - Manzella, Joseph (2000)
Keywords: dept.ant; faculty_collection; sabbatical_report

Results of an Analysis of Carnivore Tooth Mark Shape. - Selvaggio, Marie (2000)
Keywords: dept.ant; faculty_collection; sabbatical_report

Negotiating the news Indonesian press culture and power during the political crises of 1997–8 - Manzella, Joseph C (Journalism: Theory, Practice & Criticism, 2000)
Before 1998, journalists in Indonesia walked a tightrope stretched between a western ideological system that valued a free press and a system of rigid government controls. To maintain their balance, reporters and editors used strategies that were uniquely Indonesian to maintain a journalistic frame that was essentially western. This article examines those strategies in the context of the values and beliefs of print newspeople in the capital of Jakarta, focusing on news coverage of the political crises of 1997 and 1998 that culminated in the resignation of President Suharto and that unleashed a relatively free press. It contends that the contradictions and resultant conflicts between the government and newspeople in Jakarta represented a contest between western and Indonesian notions of the purposes and duties of the press. Copyright © 2000 SAGE Publications.
Keywords: Ideology of journalism; Indonesia; Occupational identity; Political change; Press; dept.ant

The new and improved clint eastwood: change and persistence in promise keepers self-help literature - Bloch, Jon P (Sociology of Religion, 2000)
Like other expressions of Christian conservatism, the Promise Keepers (PK) often enact complex and strained relationships between social change and social persistence. These strains are evident in the official PK literature, which employs techniques not unlike those used by mainstream pop psychology. These include the use of “scientific”-like classifications of information, authors presented as “experts” on the topic at hand, and the use of exercises to be enacted individually or in small PK discussion groups. Collectively, these strategies suggest that conservative Christians deal with many of the same complex role demands as non-conservatives. In Particular, the PK stance on gender roles, though Promoted as unambiguously “traditional” in favoring male leadership and female submission, in actuality often reflects acknowledgment and perhaps acceptance of some of the more egalitarian changes in gender role norms. Sociological implications and directions for future research are discussed.
Keywords: dept.ant; dept.soc